Euthanasia Dalam Perspektif Hukum Pidana Indonesia - Habibiellah Huda; Ismansyah, Ismansyah; Edita Elda (UNES Law Review, 2024)
The increasing development of technology in the health sector has led to many new things that can be done, one of which is euthanasia which is often debated in Indonesia and around the world. Euthanasia comes from the words "eu" which means good and "thanatos" which means to die, so euthanasia means to die well. Euthanasia is a very complex and complicated problem so there are parties who are for and against euthanasia. On the one hand, euthanasia causes the loss of a person's suffering because they cannot tolerate the disease they are suffering from. However, on the other hand, euthanasia causes the loss of a person's life and violates the principles of human rights. Regulations related to this matter have not been specifically regulated in Indonesian positive law. This research aims to determine euthanasia regulations from the perspective of Indonesian criminal law, euthanasia in international regulation and comparisons with other countries, as well as the reasons why euthanasia is prohibited in Indonesia. The research method used is normative legal research. The research results show that the regulation of euthanasia from the perspective of Indonesian criminal law is contained in Article 344 of the Criminal Code and Article 461 of the new Criminal Code for active euthanasia, while for passive euthanasia it is contained in Article 304 of the Criminal Code and Article 428 paragraph (1) of the new Criminal Code. In international regulation, euthanasia is not specifically regulated, but in the Declaration of Human Rights and the International Covenant on Civil and Political Rights euthanasia is contrary to the right to life, while the right to die is not regulated therein. From a comparison of 6 countries, there are countries that prohibit euthanasia, namely Indonesia, America, England and China, while the Netherlands and Germany allow euthanasia. The underlying reasons why euthanasia is prohibited in Indonesia are in the aspects of religion, positive law, court decisions, health law and human rights.